Does Environmental Management Accounting Associated with Sustainability Report Disclosure? - Odang, Nilam Kemala; Sinambela, Joseph Stevanus (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2025)
This study examines the relationship between Environmental Management Accounting (EMA) and Sustainability Report Disclosure (SRD) in energy sector firms. As businesses face increasing environmental challenges, understanding how EMA contributes to transparency in sustainability reporting is crucial. Despite prior research on EMA and SRD individually, limited empirical evidence links their direct association. This study introduces a novel approach by incorporating Monetary Environmental Management Accounting (MEMA) and Physical Environmental Management Accounting (PEMA), along with the Eco-Efficiency Index (EEI), to measure the balance between financial and environmental performance. Using a quantitative approach with multiple regression analysis on energy sector firms listed in IDX year 2023, amounted 75 firms. it confirms that EMA and EEI positively associated with SRD. The study contributes to environmental accounting literature and provides practical implications for firms and policymakers to enhance sustainability disclosures. However, limitations in sector focus and data availability suggest avenues for future research.